OP0169 The Effects of TNF Inhibitors, Methotrexate, NSAIDS and Corticosteroids on Cardiovascular Events in Rheumatoid Arthritis, Psoriasis and Psoriatic Arthritis: A Systematic Review and Meta-Analysis. (10th June 2014) - Roubille, C.; Richer, V.; Starnino, T.; McCourt, C.; McFarlane, A.; Fleming, P.; Siu, S.; Kraft, J.; Lynde, C.; Pope, J.; Keeling, S.; Gulliver, W.; et al.
Abstract : Background: Cardiovascular events (CVE) are increased in rheumatoid arthritis (RA), psoriatic arthritis (PsA) and psoriasis (PsO) patients. Objectives: To determine the impact on CVE from methotrexate (MTX), TNF inhibitors (TNFi), corticosteroids (CS) and non-steroidal anti-inflammatory drugs (NSAIDs) (non-selective [ns-]NSAIDs and coxibs) in RA, PsA, and PsO. Methods: Medline, Embase, Cochrane databases were systematically searched. Observational studies and randomized trials reporting CVE (myocardial infarction [MI], heart failure [HF], strokes, and major cardiovascular adverse effects [MACEs]) in RA and in PsA/PsO patients treated with MTX, TNFi, CS and NSAIDs were considered. Studies with <400 patients, or < one year's duration, or including patients > mean age of 80 years were excluded. Random-effects meta-analyses were performed. Results: Out of 2630 references, 34 studies were included, 28 for RA and 6 for PsA/PsO. In RA, both TNFi (RR 0.70, 95% CI, 0.54-0.90; p=0.005) and MTX (RR 0.72, 95% CI, 0.57-0.91; p=0.007) decreased all CVE. TNFi decrease MI, strokes and MACEs. MTX decreases MI. NSAIDs increased all CVE (RR 1.18, 95% CI 1.01-1.38; p=0.04) and strokes. Among NSAIDs only rofecoxib (RR 1.58, 95% CI 1.24-2.00; p<0.001) significantly impacted all CVE. CS increased all CVE (RR 1.47, 95% CI 1.34-1.60; p<0.001), MI, HF, strokes, and MACEs. In PsA/PsO, systemic therapy decreased all CVE (RR 0.75, 95% CI, 0.63-0.91; p=0.003). Conclusions: In RA, TNFi and MTX are associated with a decrease in all CVE while CS are associated with an increase of all CVE. The deleterious effect of NSAIDs on CVE is related to rofecoxib. While current evidence suggests deleterious cardiovascular effects of CS and rofecoxib in RA, targeting inflammation with MTX and TNFi may be cardioprotective. Disclosure of Interest: C. Roubille Grant/research support: This study was supported by an unrestricted grant from AbbVie. Fellowship grants/bursary from the Foundation of the University of Montreal Hospital Center (CHUM)., V. Richer Grant/research support: This study was supported by an unrestricted grant from AbbVie., T. Starnino Grant/research support: This study was supported by an unrestricted grant from AbbVie., C. McCourt Grant/research support: This study was supported by an unrestricted grant from AbbVie. Salary for the fellowship in Vancouver was funded by a Fellowship from Janssen-Ortho Canada and the British Association of Dermatology., A. McFarlane Grant/research support: This study was supported by an unrestricted grant from AbbVie., P. Fleming Grant/research support: This study was supported by an unrestricted grant from AbbVie., S. Siu Grant/research support: This study was supported by an unrestricted grant from AbbVie., J. Kraft Grant/research support: This study was supported by an unrestricted grant from AbbVie. Investigator support from Abbvie, Amgen, Galderma, Janssen, Novartis., Consultant for: Abbvie, Amgen, Galderma, Janssen, Novartis, Leo Speakers bureau: Abbvie, Amgen, Galderma, Janssen, Leo., C. Lynde Grant/research support: This study was supported by an unrestricted grant from AbbVie. Investigator support: Abbvie, Amgen, Celgene, Janssen-Ortho, Novartis, Eli Lilly, Merck, Leo Pharma., Consultant for: Abbvie, Amgen, Celgene, Janssen-Ortho, Novartis, Eli Lilly, Merck, Leo Pharma., Speakers bureau: Abbvie, Amgen, Celgene, Janssen-Ortho, Novartis, Eli Lilly, Merck, Leo Pharma, J. Pope Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research support from AbbVie, Actelion, Amgen, Astra Zeneca, Bayer, BMS, Celgene, Genentech, GSK, BMS, Jansen & Jansen, MedImmune, Mediquest, Novartis, Pfizer, Roche, United Chemicals Belgium., Consultant for: AbbVie, Actelion, Amgen, Astra Zeneca, Bayer, BMS, Celgene, Genentech, GSK, BMS, Jansen & Jansen, MedImmune, Mediquest, Novartis, Pfizer, Roche, United Chemicals Belgium., S. Keeling Grant/research support: This study was supported by an unrestricted grant from AbbVie. Unrestricted educational funding received from the following:Pfizer, Janssen, Astrazeneca, Roche., Consultant for: Participated in advisory boards as consultant for:Janssen, AbbVie, Roche, Amgen., W. Gulliver Grant/research support: study was supported by an unrestricted grant from AbbVie. Research support from Abbott/AbbVie, Actelion, Amgen, Astellas, Bio-K, Celgene, Galderma, Janssen, LEO Pharma, Merck/Schering, Novartis, Pfizer, Roche and Valeant., Consultant for: Abbott/AbbVie, Actelion, Amgen, Astellas, Bio-K, Celgene, Galderma, Janssen, LEO Pharma, Merck/Schering, Novartis, Pfizer, Roche and Valeant., Speakers bureau: Abbott/AbbVie, Actelion, Amgen, Astellas, Bio-K, Celgene, Galderma, Janssen, LEO Pharma, Merck/Schering, Novartis, Pfizer, Roche and Valeant, J. Dutz Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research support Abbvie, Centocor, Janssen- Ortho, Novartis, ONO Pharmaceuticals, Roche., Consultant for: Janssen-Ortho, AbbVie Amgen, Leo, Roche Speakers bureau: Janssen-Ortho, AbbVie Amgen, Leo., L. Bessette Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research support AbbVie, UCB, Janssen, and Amgen. Consultant for: AbbVie, UCB, Janssen, and Amgen., Speakers bureau: AbbVie, UCB, Janssen, and Amgen., R. Bissonnette Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research grants and honoraria AbbVie, Amgen, Celgene, Eli-Lilly Galderma, Incyte, Janssen, Leo Pharma, Merck, Novartis, Pfizer, Tribute., Consultant for: AbbVie, Amgen, Celgene, Eli-Lilly Galderma, Incyte, Janssen, Leo Pharma, Merck, Novartis, Pfizer, Tribute., B. Haraoui Grant/research support: This study was supported by an unrestricted grant from AbbVie. Grant support from Abbvie, Amgen, BMS, Celgene, Janssen, Pfizer, Roche, UCB., Consultant for: Abbvie, Amgen, BMS, Celgene, Janssen, Pfizer, Roche, UCB. DOI: 10.1136/annrheumdis-2014-eular.5448